Principle and benefits of third party logistics approach when managing logistics supply chain - Vasiliauskas, Aidas V.; Jakubauskas, Gražvydas (Transport, 2007)
The principle of third party logistics has grown into a very important and a well‐functioning logistics concept, mainly due to outsourcing trends in transport business. Providers of 3PL services complemented the effectiveness of logistics supply chain management extending the performance of hauliers and forwarders to what might be called outsourced logistics services providers. The main driver for this was large transportation companies that have striven to render their limited services to the whole transport chain. Firstly, this extended to what now is called forwarding services, i.e. responsibility and transport service was extended from only physical transportation to additional services. Then some transport and forwarding companies continued enlarging their responsibility so that it included an increased part of the transport chain up to a total responsibility for the entire transportation, from production to consumption. A nature of transportation services became more and more the nature of logistics. Companies started offering complete logistics solutions, instead of only isolated physical transportation services. This allowed a customer to concentrate on the core business instead of paying much attention to material flows. First Published Online: 27 Oct 2010